Praedicate Evangelium Art. 197: nuovi elementi d’identità della Segnatura Apostolica come Tribunale amministrativo - Gherri, Paolo (Apollinaris, 2022)
Introduction. 1. The Apostolic Signatura as an Administrative Tribunal for the Roman Curia. 2. The disappearance of the "illegitimacy" of the Acts from the Signatura's horizon. Conclusion.